Postural Balance among Elderly with Diabetes Mellitus: A Descriptive Study in the Geriatric Polyclinic of Level II Udayana Hospital - Dewi, Triyana Puspa; Serinadi, Desak Made; Wardani, Silvia Intan; Wisnawa, I Nyoman Dharma; Astawa, I Gede Satria (JURNAL KESEHATAN POLTEKKES KEMENKES RI PANGKALPINANG, 2025)
Background: Advancing age is often accompanied by physical decline in the elderly, including impaired balance. One of the most serious consequences of this impairment is the risk of falling. Diabetes mellitus is suspected to be a contributing factor to postural imbalance in older adults.Objective: This study aims to analyze postural balance among elderly individuals with diabetes mellitus at the Geriatric Polyclinic, Level II Udayana Hospital.Method: This quantitative study employed a cross-sectional design and involved 94 elderly patients diagnosed with diabetes mellitus at the Geriatric Polyclinic of Level II Udayana Hospital, Denpasar. Data were collected through direct observation using the Berg Balance Scale to assess postural balance. Descriptive univariate analysis was used for data interpretation.Results: Demographically, 68 respondents (72.34%) were aged 60–74, 54 (57.45%) were male, and 38 (40.42%) had completed senior high school. A majority, 62 respondents (65.96%), had lived with diabetes for more than five years. In terms of balance, 60 respondents (63.83%) were classified as independent, while 32 (34.04%) required walking assistance. The mean Berg Balance Scale score was 31.3, indicating the need for walking assistance.Conclusion: Elderly individuals with diabetes mellitus are at increased risk of postural imbalance due to aging and disease-related factors. These findings highlight the importance of early detection and may inform the development of targeted fall-prevention interventions for this population. Keywords: Elderly; Postural Balance; Diabetes Mellitus; Postural Imbalance; Berg Balance Scale.